Meta-analysis of Germline Whole-exome Sequencing in 1435 Cases of Testicular Germ Cell Tumour to Evaluate Disruptive Mutations Under Dominant, Recessive, and X-linked Inheritance Models - Zeid Kuzbari; Charlie F. Rowlands; Isaac Wade; Alice Garrett; Chey Loveday; Subin Choi; Beth Torr; Kevin Litchfield; Alison Reid; Robert Huddart; Peter Broderick; Richard S. Houlston; et al. (European Urology Open Science)
Background and objective: Testicular germ cell tumour (TGCT) is the most common cancer in young men, and over half of its high estimated heritability is unexplained. Our objective was to identify rare pathogenic germline variation driving TGCT susceptibility. Methods: This study is a case-control meta-analysis of whole-exome sequencing data from three datasets (Institute of Cancer Research, The Cancer Genome Atlas, and UK Biobank). We retained unrelated male individuals of European ancestry comprising 1435 TGCT cases and 18 284 cancer-free controls. We performed gene-level association testing of protein-truncating variants and nonsynonymous disruptive variants across six candidate gene sets (733 genes) potentially biologically related to TGCT. We then analysed exome wide (19 355 genes) under dominant and recessive models, including X-linked genes. Key findings and limitations: No individual gene-disease association was identified following multiple testing corrections. However, functional gene-set analyses identified an excess of associations with genes involved in microtubular/ciliary pathways (p = 1.69 × 10–8). Our study was well powered to detect rare variation of moderate/high effect sizes (odds ratio [OR] ≥5), but power diminished for modest effect sizes (OR <5). Conclusions and clinical implications: Although this is the largest whole-exome analysis of TGCT to date and first exome-wide examination for recessively acting gene associations, larger studies are required to identify robust associations for individual genes. Patient summary: We investigated samples from 1435 men with testicular cancer and 18 284 men without cancer to compare the rate of disruptive mutations in 19 355 genes. No evidence of specific genes associated with testicular cancer was discovered, although one gene group showed a strong association. Larger studies are needed to identify individual genes associated with causing testicular cancer.